Anestesi Umum pada Pasien dengan Retensio Plasenta dan Perdarahan Postpartum: Laporan Kasus - I Made Ananta Wiguna (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2026)
Postpartum hemorrhage remains the leading cause of maternal mortality in developing countries and is frequently associated with obstetric emergencies requiring prompt and appropriate management. One of the important etiologies is retained placenta, which can result in massive bleeding, hypovolemic shock, and hemodynamic instability, thereby necessitating immediate operative intervention. Anesthetic management in this condition is challenging because it must consider the patient’s intravascular volume status, the risk of aspiration, physiological changes during pregnancy, and the need for optimal airway protection. This case report describes a female patient with retained placenta and postpartum hemorrhage who underwent emergency curettage under general anesthesia with endotracheal intubation. The anesthetic approach included fluid resuscitation, close hemodynamic monitoring, selection of cardiovascularly stable induction agents, and controlled ventilation to maintain adequate oxygenation and prevent aspiration. Endotracheal intubation was chosen as the standard airway management technique in obstetric emergencies because it provides effective ventilation control and protection against gastric content regurgitation. Intraoperative management resulted in stable vital signs without anesthetic complications and improved hemodynamic status postoperatively. This report highlights the importance of rapid, well-planned, and multidisciplinary anesthetic management to enhance maternal safety in cases of retained placenta with postpartum hemorrhage.